Understanding Nurses Experiences and Perception about The Implemention of Emergency Monitoring : A Qualitative Study - Kholis, Anja Hesnia; Hidayah, Nurul; Priyanti, Ratna Puji; Asri, Asri; Ellina, Agusta Dian (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2020)
ABSTRACTEmergency monitoring in the hospital is very important to be carried out, as one form of responsibility for early detection of deterioration patients. The implementation of the Early Warning System in Hospital is still being evaluated by the quality of service to find out its effectiveness. The purpose of this study was to explore the experiences and perceptions of nurses about the implementation of emergency monitoring in hospital. This study was a qualitative design. Participants were 6 female team leader nurses, with average age 35.3 y.o, and average working experience 11.3 years, used purposive sampling. Data were collected by in-depth interviews and field notes. Data were analyzed using thematic analysis method by Flick. The findings of the study identified 3 themes: (1) personal themes; (2) environmental themes; (3) Patient themes. The results showed that the implementation of emergency monitoring in the inpatients units in hospital was still not optimal. The implementation of the Early Warning System is expected to be carried out on an ongoing basis so that its implementation is effective. Socialization, training, supervision, and adequate infrastructure are needed as well as consistency algorithms for early identification of the patient's condition and getting immediate assistance.ABSTRAK Pemantauan kedaruratan di rumah sakit sangat penting dilakukan, sebagai salah satu bentuk tanggung jawab untuk deteksi dini kemunduran pasien. Penerapan Sistem Peringatan Dini di Rumah Sakit masih terus dievaluasi kualitas pelayanannya untuk mengetahui efektivitasnya. Penelitian ini bertujuan untuk mengetahui pengalaman dan persepsi perawat tentang pelaksanaan pemantauan kegawatdaruratan di rumah sakit. Penelitian ini merupakan penelitian kualitatif. Peserta penelitian adalah 6 perawat ketua tim wanita, dengan usia rata-rata 35,3 tahun, dan pengalaman kerja rata-rata 11,3 tahun, menggunakan purposive sampling. Pengumpulan data dilakukan dengan wawancara mendalam dan catatan lapangan. Data dianalisis menggunakan metode analisis tematik oleh Flick. Temuan penelitian mengidentifikasi 3 tema: (1) tema pribadi; (2) tema lingkungan; (3) Tema pasien. Kesimpulan: Hasil penelitian menunjukkan bahwa pelaksanaan pemantauan kegawatdaruratan di unit rawat inap rumah sakit masih belum optimal. Penerapan Sistem Peringatan Dini diharapkan dapat dilakukan secara berkesinambungan agar pelaksanaannya efektif. Dibutuhkan sosialisasi, pelatihan, supervisi, dan infrastruktur yang memadai serta konsistensi algoritme untuk identifikasi awal kondisi pasien dan mendapatkan bantuan segera.